Impact of Cash Management on Profitability in Small Manufacturing Organization - Pandey, Dhruba Lal (Pravaha, 2020)
Small businesses are vital for economic development and employment generation. The implementation of sound cash management practices is essential to ensure the profitability. The aim of the study was to identify the impact of cash management on profitability. This study was adopted correlation research design. Purposive sampling method was adopted while undertaking research. 80 samples were considered while collecting data. The sample structure consisted of small and medium manufacturing businesses in the Kirtipur Municipality. Owners of such enterprises were taken as sample because they can better understand the cash management. Data were collected using five point Likert Scale Questionnaires. Data were analyzed using mean, correlation and regression models. Study found that Cash management has an insignificant but positive effect on profitability. It clarifies that conversion cycle, cash flow and inventory manage positively effects to the profitability but the effect is nominal.